Proposal for a systematic analysis of polygraphy or polysomnography for identifying and scoring abnormal events occurring during non-invasive ventilation. Issue 6 (22nd October 2010) - Gonzalez-Bermejo, J; Perrin, C; Janssens, J P; Pepin, J L; Mroue, G; Léger, P; Langevin, B; Rouault, S; Rabec, C; Rodenstein, D; ,
Abstract : Non-invasive ventilation (NIV) is recognised as an effective treatment for chronic hypercapnic respiratory failure. Monitoring NIV during sleep may be preferable to daytime assessment. This paper reports the findings of an international consensus group which systematically analysed nocturnal polygraphic or polysomnographic tracings recorded with either volume-cycled or pressure-cycled ventilators. A systematic description of nocturnal respiratory events which occur during NIV is proposed: leaks, obstruction at different levels of the upper airway (glottis and/or pharynx), with or without decrease of respiratory drive and asynchrony.